Changes of adenosinergic system in piglets fed a diet co-contaminated by mycotoxin and their effects on the regulation of adenosine - Souza C.F. (2018)
© 2017 Elsevier LtdThe effects of diets co-contaminated with 300 μg/kg of aflatoxins and 8000 μg/kg of fumonisins on adenosinergic system of the pigs weaned at 15 days of age were studied. Piglets were inspected daily, and body weight measurement and blood collections were performed at every five days. Piglets intoxicated by mycotoxins presented lower weight gain (p < 0.001) in comparison to control. Intoxicated piglets also showed a reduction in the serum levels of zinc and adenosine and in adenosine deaminase (ADA) activity (p < 0.001). Positive correlations between zinc levels and ADA activity (p < 0.001) and between adenosine levels and ADA activity (p < 0.05) were observed. Ternary plot shows the influence of zinc levels on ADA activity and on adenosine levels, suggesting that low zinc levels, caused by subclinical mycotoxin intoxication, can cause immunomodulatory effects in piglets. We conclude that piglets intoxicated by fumonisins and aflatoxins have low ADA activity and adenosine levels in serum. This can be directly related to zinc reduction, which is a cofactor for ADA. The co-contamination by these mycotoxins in piglet feed impairs growth and immune defenses of the animals, adversely affecting animal health and production. Therefore, changes in the purinergic pathway may affect the pathogenesis of the disease.